2019
DOI: 10.1111/ctr.13692
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with infection related to a ventricular assist device after heart transplantation

Abstract: Background: Despite significant advances in durable mechanical support survival, infectious complications remain the most common adverse event after ventricular assist device (VAD) implantation and the leading cause of early death after transplantation. In this study, we aim to describe our local infectious epidemiology and review short-term survival and infectious incidence rates in the post-transplantation period and assess risk factors for infectious episodes after transplantation. Methods: Retrospective si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Posttransplant survival of a patient with pretransplant LVAD infection has been explored in several recent studies. Similar to our study findings, no significant difference was observed when compared with cases without an LVAD infection [ 19 ]. Therefore, active or suppressed LVAD infection should not dissuade or delay patients and physicians from proceeding with heart transplantation if an organ becomes available.…”
Section: Discussionsupporting
confidence: 91%
“…Posttransplant survival of a patient with pretransplant LVAD infection has been explored in several recent studies. Similar to our study findings, no significant difference was observed when compared with cases without an LVAD infection [ 19 ]. Therefore, active or suppressed LVAD infection should not dissuade or delay patients and physicians from proceeding with heart transplantation if an organ becomes available.…”
Section: Discussionsupporting
confidence: 91%
“…The present study focused on changes in the BMI during the initial period of hospitalization after LVAD implantation and showed that a reduction infectious complications even after heart transplantation. 21 The present study provides further evidence that a reduction in BMI during the initial period of hospitalization after LVAD implantation is independently associated with a higher incidence of LVAD-specific infection within 1 year after implantation. In particular, patients with a low serum albumin concentration at baseline may be at high risk of developing LVAD-specific infections when their BMI decreases.…”
Section: Factors Associated With the Incidence Of Lvad-specific Infectionsupporting
confidence: 65%
“…The incidence was the highest in patients with LVAD infections and LVAD bleeding complications and T patients. While a correlation between LVAD infections and postoperative infective constellations might be mediated by systemic inflammation, a correlation with bleeding events and T group is not completely understood at present 10,27 . We can only suggest a role of the acquired von Willebrand syndrome, frequently observed in patients with prolonged durable MCS 28 …”
Section: Discussionmentioning
confidence: 88%
“…While a correlation between LVAD infections and postoperative infective constellations might be mediated by systemic inflammation, a correlation with bleeding events and T group is not completely understood at present. 10,27 We can only suggest a role of the acquired von Willebrand syndrome, frequently observed in patients with prolonged durable MCS. 28 Primary graft dysfunction is a common problem in HTx and associated with impaired survival.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation